Temporal trends in presentations to Victorian EDs for stroke and TIAs - the impact of public awareness campaigns - Bray, Janet; Finn, Judith; Cameron, P.; Smith, K.; Straney, L.; Nehme, Z.; Bladin, C. (SAGE PUBLICATIONS LTD, 2017)
Introduction: Since 2004, the Stroke Foundation have run annual public awareness campaigns in Australia −using the FAST (Face, Arm, Speech Time) message since 2006. The FAST campaigns have increased awareness of stroke symptoms and calls to ambulance for stroke. In this study we examined the impact of the campaigns on the way stroke and TIA patients present to Victorian public emergency departments (EDs). Methods: Using the Victorian Emergency Minimum Dataset (VEMD) provided by the Department of Health and Human Services, we examined trends in presentations for patients with an emergency diagnosis of stroke or TIA admitted between 2003 and 2014. Annual trends were examined using logistic regression adjusting for age, sex, metropolitan hospital and English as preferred language (adjusted odd ratios, AOR). Results: Of the 13,496,434 VEMD admissions, almost 0.9% received an ED diagnosis of stroke (n = 71,791) or TIA (n = 46,291). Compared to 2003, significant changes were seen in referral patterns and in the transport used in the years the FAST message featured: a decrease in patients presenting via local doctors (p < 0.001, in 2014 AOR = 0.51); an increase in patients self-referring (p < 0.001, in 2014 AOR = 1.62); and, an increase in ambulance use (p < 0.001, in 2014 AOR = 1.12). Similar trends were seen in stroke and TIA patients. In 2014, 80% of stroke patients presented to a stroke thrombolysis centre (77% in self-transported and 84% in ambulance-transported). Conclusion: Since the FAST campaigns began, a greater proportion of stroke and TIA patients are presenting to hospital via ambulance and are bypassing their local doctors.